Emotional expressions preferentially elicit implicit evaluations of faces also varying in race or age - Craig, B.; Lipp, Ottmar; Mallan, K. (American Psychological Association, 2014)
Both facial cues of group membership (race, age, and sex) and emotional expressions can elicit implicitevaluations to guide subsequent social behavior. There is, however, little research addressing whethergroup membership cues or emotional expressions are more influential in the formation of implicitevaluations of faces when both cues are simultaneously present. The current study aimed to determinethis. Emotional expressions but not race or age cues elicited implicit evaluations in a series of affectivepriming tasks with emotional Caucasian and African faces (Experiments 1 and 2) and young and old faces (Experiment 3). Spontaneous evaluations of group membership cues of race and age only occurred when those cues were task relevant, suggesting the preferential influence of emotional expressions in the formation of implicit evaluations of others when cues of race or age are not salient. Implications for implicit prejudice, face perception, and person construal are discussed.